Destination integration: linking physiology, histology, and embryology content in foundational sciences - Dennis, Jennifer F.; Creamer, Bradley A. (Frontiers in Physiology, 2023)
Anatomy and physiology are tightly linked disciplines that complement each other, however, in medical education delivery of this content is often siloed and divided. To address this, we created combined anatomy and physiology content for the female reproductive system, and team-taught designated histology and embryology topics integrated with the physiology content. Collectively, this created a more holistic incorporation of topics for student learning. Here we describe the format and approach for this teaching innovation.